East Africa: seed policies - Minde, Isaac (International Food Policy Research Institute, 2006)
The countries of Eastern and Central Africa are heavily dependent on agriculture, and seeds are a key input in agricultural production. Yet in each country in Eastern and Central Africa, the seed industry faces different laws, standards, and regulations, w